The Investigation of Dissociation of Trifluoroacetyl Fluoride in the Field of Pulsed CO2 Laser. Issue 6 (1986) - Aslanidi, E. B.; Zarubin, V. T.; Turishchev, Yu. S.
Abstract : CF3 COF dissociation channels in the pressure region from 0.2 to 4 Torr under the pulsed CO2 laser radiation are investigated. The dissociation products COF2, C2 F6, and CF4 are identified according to the infrared spectra, and their relative output is measured over the whole range of the initial substance pressures. A scheme of laserochemical reactions describing the trifluoroacetyl fluoride dissociation channels is presented. The correctness of the chosen scheme is confirmed on the basis of the elementary theory of active collisions. The measurements of CF3 COF dissociation selectivity for 18 O and 13 C are given.